Safety and Outcome of Revascularization Treatment in Patients With Acute Ischemic Stroke and COVID-19: The Global COVID-19 Stroke Registry. (14th February 2023) - Marto, João Pedro; Strambo, Davide; Ntaios, George; Nguyen, Thanh N.; Herzig, Roman; Czlonkowska, Anna; Demeestere, Jelle; Mansour, Ossama Yassin; Salerno, Alexander; Wegener, Susanne; Baumgartner, Philipp; Cereda, Carlo W.; et al.
Abstract : Background and Objectives: COVID-19–related inflammation, endothelial dysfunction, and coagulopathy may increase the bleeding risk and lower the efficacy of revascularization treatments in patients with acute ischemic stroke (AIS). We aimed to evaluate the safety and outcomes of revascularization treatments in patients with AIS and COVID-19. Methods: This was a retrospective multicenter cohort study of consecutive patients with AIS receiving intravenous thrombolysis (IVT) and/or endovascular treatment (EVT) between March 2020 and June 2021 tested for severe acute respiratory syndrome coronavirus 2 infection. With a doubly robust model combining propensity score weighting and multivariate regression, we studied the association of COVID-19 with intracranial bleeding complications and clinical outcomes. Subgroup analyses were performed according to treatment groups (IVT-only and EVT). Results: Of a total of 15, 128 included patients from 105 centers, 853 (5.6%) were diagnosed with COVID-19; of those, 5, 848 (38.7%) patients received IVT-only and 9, 280 (61.3%) EVT (with or without IVT). Patients with COVID-19 had a higher rate of symptomatic intracerebral hemorrhage (SICH) (adjusted OR 1.53; 95% CI 1.16–2.01), symptomatic subarachnoid hemorrhage (SSAH) (OR 1.80; 95% CI 1.20–2.69), SICH and/or SSAH combined (OR 1.56; 95% CI 1.23–1.99), 24-hour mortality (OR 2.47; 95% CI 1.58–3.86), and 3-month mortality (OR 1.88; 95% CI 1.52–2.33). Patients with COVID-19 also had an unfavorable shift in the distribution of the modified Rankin score at 3 months (OR 1.42; 95% CI 1.26–1.60). Discussion: Patients with AIS and COVID-19 showed higher rates of intracranial bleeding complications and worse clinical outcomes after revascularization treatments than contemporaneous non–COVID-19 patients receiving treatment. Current available data do not allow direct conclusions to be drawn on the effectiveness of revascularization treatments in patients with COVID-19 or to establish different treatment recommendations in this subgroup of patients with ischemic stroke. Our findings can be taken into consideration for treatment decisions, patient monitoring, and establishing prognosis. Trial Registration Information: The study was registered under ClinicalTrials.gov identifier NCT04895462.